Development of an intein-mediated split–Cas9 system for gene therapy - Truong, Dong-Jiunn Jeffery (Nucleic Acids Res, 2015)
Using CRISPR/Cas9, it is possible to target virtually any gene in any organism. A major limitation to its application in gene therapy is the size of Cas9 (>4 kb), impeding its efficient delivery via recombinant adeno-associated virus (rAAV). Therefore, we developed a split–Cas9 system, bypassing the packaging limit using split-inteins. Each Cas9 half was fused to the corresponding split-intein moiety and, only upon co-expression, the intein-mediated trans-splicing occurs and the full Cas9 protein is reconstituted. We demonstrated that the nuclease activity of our split-intein system is comparable to wild-type Cas9, shown by a genome-integrated surrogate reporter and by targeting three different endogenous genes. An analogously designed split-Cas9D10A nickase version showed similar activity as Cas9D10A. Moreover, we showed that the double nick strategy increased the homologous directed recombination (HDR). In addition, we explored the possibility of delivering the repair template accommodated on the same dual-plasmid system, by transient transfection, showing an efficient HDR. Most importantly, we revealed for the first time that intein-mediated split–Cas9 can be packaged, delivered and its nuclease activity reconstituted efficiently, in cells via rAAV.